Setting Priorities in the Age of Austerity British, French, and German Experiences - Shurkin, Michael (RAND Corporation, 2013)
Examines the British, French, and German armies' approaches to accommodating significant budget cuts while attempting to sustain their commitment to full spectrum operations. Specifically, it looks at the choices these armies are making with respect to how they spend dwindling resources: What force structure do they identify as optimal? How much readiness do they regard as necessary? Which capabilities are they abandoning?